2011
DOI: 10.1016/j.bbamcr.2010.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 proteins and mitochondria—Specificity in membrane targeting for death

Abstract: The localization and control of Bcl-2 proteins on mitochondria is essential for the intrinsic pathway of apoptosis. Anti-apoptotic Bcl-2 proteins reside on the outer mitochondrial membrane (OMM) and prevent apoptosis by inhibiting the activation of the pro-apoptotic family members Bax and Bak. The Bcl-2 subfamily of BH3-only proteins can either inhibit the anti-apoptotic proteins or directly activate Bax or Bak. How these proteins interact with each other, the mitochondrial surface and within the OMM are compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
248
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(257 citation statements)
references
References 97 publications
7
248
0
2
Order By: Relevance
“…Bcl-2 family proteins regulate mitochondrion-dependent apoptosis by influence on the permeability of MOM (29). Apoptosis-associated MOMP is known to require pro-apoptotic Bax-like proteins (in regulation of the formation of pores in the mitochondria) and anti-apoptotic Bcl-2-like proteins (functionally distinct from their role in mitochondrial morphogenesis) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 family proteins regulate mitochondrion-dependent apoptosis by influence on the permeability of MOM (29). Apoptosis-associated MOMP is known to require pro-apoptotic Bax-like proteins (in regulation of the formation of pores in the mitochondria) and anti-apoptotic Bcl-2-like proteins (functionally distinct from their role in mitochondrial morphogenesis) (30).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that PRL-induced BCLXL is needed for its pro-survival effect against DEX-induced cell death in INS-1 cells [26]. The BCL family of proteins is a major regulator of the intrinsic mitochondrial cell death pathway [43]. Considering that both DEX and GLT mediate their toxic effects through the intrinsic cell death pathway [44,45], it is not surprising that BCLXL, an anti-apoptotic member of the BCL family, is protective against both cell death inducers.…”
Section: Discussionmentioning
confidence: 99%
“…Z designates a stop codon. Adapted from Lindsay et al (2011) Membrane binding properties of the C-terminal domain of Bcl-2 family proteins…”
Section: Mode 1 Inhibiɵonmentioning
confidence: 99%